Analysis Of Flexural Resistance And Environmental Feasibility Of Ferrocement Concrete Slabs From Fly Ash And Sandblasting Waste - Luqman Cahyono; Dwi Pratiwi, Wiwik; Fardina, Firda; Widiana, Dika Rahayu; Carina, Annisa' (Jurnal Teknologi Maritim, 2025)
Sandblasting waste from the shipbuilding industry and fly ash waste from industry and electric steam power plants in Indonesia are relatively high in quantity, are B3, and can potentially cause serious environmental pollution. This research aims to utilize this waste as material for ferrocement concrete, where the SiO2 and Al2O3 content from fly ash replaces some of the cement, silica sand from sandblasting waste replaces sand, and additional wire mesh as reinforcement. The method used is a quantitative experiment, where the material to be used is tested for gradation and TCLP. The finished ferrocement concrete is tested for flexural strength. The test results show that the raw material meets the gradation standards in SNI 03 2834 2000, as well the TCLP test results which show that the B3 heavy metal content is Barium, Zinc, and Copper in the sandblasting waste value is below the quality standards of PP No. 22 of 2021 Appendix XI so that all materials can be used for mix designs. The mix design created has a composition ratio of 1S:1.5PB, 1S:1.5PB:50AT, 1S:2PB, and 1S:1PB:50AT. The 1S:2PB ratio composition has the highest average flexural strength, namely 17.46 MPa, which is suitable for light vertical load construction work